Electrolyte precursor and preparation method thereof, battery and preparation method thereof

By using electrolyte precursors composed of lithium salts, ionic liquids and prepolymers in lithium metal batteries, a gel electrolyte with a three-dimensional cross-linked network structure is formed, and the problem of poor circulation and safety performance of lithium metal batteries is solved, thus realizing the It can improve the overall performance of the battery.

CN119153774BActive Publication Date: 2025-02-25JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411625397.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The circulation and safety performance of existing lithium metal batteries are poor, mainly due to the high reactive activity of metal lithium, which leads to excessive growth of lithium dendrites and changes in the volume of negative electrode materials, which in turn affects the reversibility of lithium deposition and peeling, and poses safety hazards.

Method used

Using an electrolyte precursor, including lithium salts, ionic liquids and prepolymers, the ionic liquids contain hexafluorophosphate and tetrafluoroborate, and the prepolymer is passed through cross-linking polymerization of the first monomer and the second monomer. The gel electrolyte formed has a three-dimensional cross-linked network structure, both rigid and flexible.

Benefits of technology

The gel electrolyte formed can effectively inhibit the growth of lithium dendrites, adapt to the volume changes of the negative electrode material, improve the uniform deposition and peeling of lithium ions, and improve the circulation and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153774B_ABST
    Figure CN119153774B_ABST
Patent Text Reader

Abstract

The present application relates to an electrolyte precursor and a preparation method thereof, a battery and a preparation method thereof, wherein the electrolyte precursor comprises a lithium salt, an ionic liquid and a prepolymer; the ionic liquid comprises at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinium ionic liquid containing hexafluorophosphate, and a pyrrolidinium ionic liquid containing tetrafluoroborate. In this way, the electrochemical stability and interfacial chemical stability of the gel electrolyte can be improved, thereby effectively improving the cycle performance and safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte precursor and a preparation method thereof, a battery and a preparation method thereof. Background Art

[0002] For secondary batteries, the specific capacity of existing graphite negative electrodes has reached its limit. In order to further improve the energy density, a new generation of negative electrode materials is needed. The theoretical specific capacity of metallic lithium is 3860mAh / g, which is 10 times higher than that of graphite, and has a lower electrode potential (-3.04V), making it suitable as a negative electrode material for lithium batteries.

[0003] Due to the high reactivity of metallic lithium, the side reactions between lithium metal anode and electrolyte are serious, and the solid electrolyte interface film formed at the interface between the anode and electrolyte is unstable, which can easily lead to excessive growth of lithium dendrites and drastic volume changes of the anode material, ultimately leading to poor reversibility of lithium deposition and stripping, and potential safety hazards, which hinder the application of lithium metal batteries. Therefore, how to improve the cycle performance and safety performance of lithium metal batteries is an urgent problem to be solved. Summary of the invention

[0004] In view of this, the embodiments of the present application provide an electrolyte precursor and a preparation method thereof, a battery and a preparation method thereof to solve at least one problem existing in the background technology.

[0005] In a first aspect, an embodiment of the present application provides an electrolyte precursor, comprising a lithium salt, an ionic liquid and a prepolymer;

[0006] The ionic liquid includes at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinium ionic liquid containing hexafluorophosphate, and a pyrrolidinium ionic liquid containing tetrafluoroborate;

[0007] The structural formula of the prepolymer is shown in formula (I):

[0008] ;

[0009] Formula I

[0010] Wherein, a, b, c, m and n are all natural numbers, and R is a H atom or a methyl group.

[0011] In conjunction with the first aspect of the present application, in an optional embodiment, the electrolyte precursor satisfies at least one of the following characteristics:

[0012] (1) The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate;

[0013] (2) The ionic liquid includes at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate, N-alkyl-N-methylpiperidinium tetrafluoroborate, N-alkyl-N-methylpyrrolidine hexafluorophosphate, and N-alkyl-N-methylpyrrolidine tetrafluoroborate;

[0014] (3) The ratio of the mass of the lithium salt to the mass of the ionic liquid is 1:(5-10);

[0015] (4) The ratio of the mass of the prepolymer to the mass of the ionic liquid is (0.05-0.15): 1;

[0016] (5) The prepolymer comprises a cross-linked product of a first monomer and a second monomer, wherein the first monomer comprises at least one of the compounds having a structure represented by formula (II), and the second monomer comprises at least one of the compounds having a structure represented by formula (III);

[0017] ;

[0018] Formula II

[0019] ;

[0020] Formula III

[0021] Wherein, a, b and c are all natural numbers, and R is a H atom or a methyl group.

[0022] In a second aspect, an embodiment of the present application provides a method for preparing an electrolyte precursor, comprising the following steps:

[0023] S1: mixing a first monomer, a second monomer, an initiator and a solvent to perform a first cross-linking polymerization reaction to form a prepolymer;

[0024] The first monomer includes at least one of the compounds having a structure as shown in formula (II), and the second monomer includes at least one of the compounds having a structure as shown in formula (III);

[0025] ;

[0026] Formula II

[0027] ;

[0028] Formula III

[0029] Wherein, a, b and c are all natural numbers, and R is a H atom or a methyl group;

[0030] S2: Evenly mix the lithium salt, the ionic liquid and the prepolymer to obtain the electrolyte precursor, wherein the ionic liquid includes at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinyl ionic liquid containing hexafluorophosphate and a pyrrolidinyl ionic liquid containing tetrafluoroborate.

[0031] In conjunction with the second aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features:

[0032] (1) The first monomer includes 2-methoxyethyl 2-acrylate;

[0033] (2) the second monomer includes glycidyl methacrylate;

[0034] (3) The initiator includes at least one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide;

[0035] (4) The solvent includes at least one of N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, and toluene;

[0036] (5) The ratio of the total mass of the first monomer and the second monomer to the mass of the solvent is 1:(2-5);

[0037] (6) The ratio of the mass of the first monomer to the mass of the second monomer is 1:(1-5);

[0038] (7) The ratio of the total mass of the first monomer and the second monomer to the mass of the initiator is 1:(0.01-0.02);

[0039] (8) The temperature of the first cross-linking polymerization reaction is 60°C to 90°C;

[0040] (9) The time of the first cross-linking polymerization reaction is 12h~36h.

[0041] In conjunction with the second aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features:

[0042] (1) The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate;

[0043] (2) The ionic liquid includes at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate, N-alkyl-N-methylpiperidinium tetrafluoroborate, N-alkyl-N-methylpyrrolidine hexafluorophosphate, and N-alkyl-N-methylpyrrolidine tetrafluoroborate;

[0044] (3) The ratio of the mass of the lithium salt to the mass of the ionic liquid is 1:(5-10);

[0045] (4) The ratio of the mass of the prepolymer to the mass of the ionic liquid is (0.05-0.15):1.

[0046] In conjunction with the second aspect of the present application, in an optional embodiment, after step S1, the method for preparing the electrolyte precursor further includes:

[0047] The prepolymer is added into the solvent for washing to remove the residual initiator, the first monomer and the second monomer.

[0048] In a third aspect, an embodiment of the present application provides a battery comprising a gel electrolyte, wherein the gel electrolyte is obtained by heating the electrolyte precursor described in any one of the first aspects or the electrolyte precursor prepared by the preparation method described in any one of the second aspects.

[0049] In a fourth aspect, an embodiment of the present application provides a method for preparing a battery, comprising the following steps:

[0050] Providing a battery cell, the battery cell comprising a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence;

[0051] The electrolyte precursor described in any one of the first aspects or the electrolyte precursor prepared by the preparation method described in any one of the second aspects is added to the battery core, and a second cross-linking polymerization reaction is carried out under heating conditions to form a gel electrolyte in the battery core.

[0052] In conjunction with the fourth aspect of the present application, in an optional implementation manner, the method satisfies at least one of the following features:

[0053] (1) The temperature of the second cross-linking polymerization reaction is 70°C to 90°C;

[0054] (2) The time of the second cross-linking polymerization reaction is 0.5h~5h;

[0055] (3) The negative electrode sheet includes metallic lithium.

[0056] In a fifth aspect, an embodiment of the present application provides a battery, which is manufactured using the battery manufacturing method described in the fourth aspect.

[0057] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0058] The electrolyte precursor and preparation method thereof, battery and preparation method thereof provided in the embodiment of the present application, the electrolyte precursor comprises a lithium salt, an ionic liquid and a prepolymer; the ionic liquid comprises at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinium ionic liquid containing hexafluorophosphate, and a pyrrolidinium ionic liquid containing tetrafluoroborate. The hexafluorophosphate (PF6 - ) and / or tetrafluoroborate (BF4 - ) The strong Lewis acid (PF5 and / or BF3) generated by thermal decomposition can be used as a cationic polymerization initiator to initiate the epoxy ring-opening polymerization in the prepolymer. Therefore, the subsequent heating of the electrolyte precursor can form a gel electrolyte through a polymerization reaction without the need to add additional initiators, which can avoid the problem of initiator residues causing deterioration of battery performance. The piperidine or pyrrolidino cations in the ionic liquid have a relatively negative reduction potential, which can improve the electrochemical stability and interfacial chemical stability of the gel electrolyte, thereby ensuring the battery's cycle performance. In addition, the gel electrolyte formed by the above-mentioned electrolyte precursor contains multiple ether oxygen bonds, which can react with Li + To coordinate and complex, enhance Li + The migration of lithium ions is improved, the ionic conductivity is improved, and the uniform deposition and stripping of lithium ions are promoted. In addition, the three-dimensional cross-linked network structure of the gel electrolyte has both rigid segments and flexible segments, so that the gel electrolyte can be used as an artificial protective layer for the negative electrode material. During the cycle, it can better inhibit the growth of lithium dendrites and adapt to the large volume changes of the negative electrode material, thereby effectively improving the cycle performance and safety performance of the battery.

[0059] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0061] Figure 1 A schematic diagram of a process for preparing an electrolyte precursor provided in an embodiment of the present application;

[0062] Figure 2 A schematic diagram of a process for preparing a battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0063] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0064] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0065] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "a", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0066] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0067] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0068] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0069] In order to improve the cycle performance and safety performance of lithium metal batteries, research on safe and stable electrolytes compatible with metallic lithium has been proven to be a very effective solution. The inventors have found that gel electrolytes can firmly lock the liquid part of the gel that acts as an electrolyte and present a colloidal semi-solid state. It can not only avoid the leakage of liquid electrolytes, but also has high ionic conductivity, which can reduce concentration polarization during battery cycling. Using gel electrolytes in lithium metal batteries can inhibit the growth of lithium dendrites to a certain extent and improve the cycle performance and safety performance of the battery. However, the performance of gel electrolytes still needs to be further improved.

[0070] Based on this, an embodiment of the present application provides an electrolyte precursor, which includes a lithium salt, an ionic liquid and a prepolymer; the ionic liquid includes at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinyl ionic liquid containing hexafluorophosphate, and a pyrrolidinyl ionic liquid containing tetrafluoroborate; the structural formula of the prepolymer is shown in formula (I):

[0071] ;

[0072] Formula I

[0073] Wherein, a, b, c, m and n are all natural numbers, and R is a H atom or a methyl group.

[0074] In the present application, the hexafluorophosphate (PF6 - ) and / or tetrafluoroborate (BF4 - ) The strong Lewis acid (PF5 and / or BF3) produced by thermal decomposition can be used as a cationic polymerization initiator to initiate the epoxy ring-opening polymerization in the prepolymer. Therefore, the subsequent heating of the electrolyte precursor can form a gel electrolyte through a polymerization reaction without the need to add additional initiators, which can avoid the problem of initiator residues causing battery performance deterioration. The piperidine or pyrrolidino cations in the ionic liquid have a relatively negative reduction potential, which can improve the electrochemical stability and interfacial chemical stability of the gel electrolyte, thereby ensuring the battery's cycle performance. Moreover, the gel electrolyte formed by the polymerization of the prepolymer contains multiple ether oxygen bonds, which can react with Li + To coordinate and complex, enhance Li + The migration of lithium ions is improved, the ionic conductivity is improved, and the uniform deposition and stripping of lithium ions are promoted. The three-dimensional cross-linked network structure of the gel electrolyte has both rigid segments and flexible segments, which can make the gel electrolyte have good structural stability and elasticity. The gel electrolyte can be used as an artificial protective layer for the negative electrode material. It can better inhibit the growth of lithium dendrites during the cycle and can adapt to the large volume changes of the negative electrode material, thereby effectively improving the cycle performance and safety performance of the battery.

[0075] The lithium salt in the electrolyte precursor is used to provide mobile lithium ions in the subsequently formed gel electrolyte. Exemplarily, the lithium salt may include at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate.

[0076] The ionic liquid in the electrolyte precursor can play the role of solvent and ion conduction. For example, the ionic liquid can include at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate (structural formula shown in Formula IV), N-alkyl-N-methylpiperidinium tetrafluoroborate (structural formula shown in Formula V), N-alkyl-N-methylpyrrolidine hexafluorophosphate (structural formula shown in Formula VI), and N-alkyl-N-methylpyrrolidine tetrafluoroborate (structural formula shown in Formula VII).

[0077] ;

[0078] Formula IV

[0079] ;

[0080] Formula V

[0081] ;

[0082] Formula VI

[0083] ;

[0084] Formula VII

[0085] In the above formula IV, formula V, formula VI and formula VII, n is an integer between 1 and 5, for example, it can be 1, 2, 3, 4 or 5.

[0086] The ionic liquid in the embodiment of the present application can play the role of an initiator in the subsequent process of forming a gel electrolyte, initiating a cross-linking polymerization reaction of the prepolymer, that is, a gel electrolyte can be formed without the need to add an additional initiator. In this way, the problem of deterioration of battery performance due to residual initiator can be avoided. Moreover, the piperidine or pyrrolidyl cation in the ionic liquid has a relatively negative reduction potential, and therefore has a wider electrochemical window. The wider the electrochemical window, the better the stability, so that the ionic liquid has a low melting point, high thermal stability and a high electrochemical window, which can improve the thermal stability and electrochemical window of the subsequently formed gel electrolyte, thereby better ensuring the cycle performance of the battery.

[0087] More specifically, the ionic liquid may include at least one of N-propyl-N-methylpiperidinium hexafluorophosphate (CAS: 1426821-81-9), N-ethyl-N-methylpiperidinium tetrafluoroborate (CAS: 117947-87-2), N-propyl-N-methylpyrrolidine hexafluorophosphate (CAS: 327022-58-2), and N-ethyl-N-methylpyrrolidine tetrafluoroborate (CAS: 117947-85-0).

[0088] When the ratio of the mass of the lithium salt to the mass of the ionic liquid is small, the content of the lithium salt in the electrolyte precursor is relatively low, and the content of the ionic liquid is relatively high, which will reduce the number of mobile lithium ions in the gel electrolyte formed subsequently, thereby affecting the capacity and other performance of the battery. When the ratio of the mass of the lithium salt to the mass of the ionic liquid is large, the content of the ionic liquid in the electrolyte precursor is relatively low, and the content of the lithium salt is relatively high. The low content of the ionic liquid will affect the thermal stability and electrochemical window of the gel electrolyte formed subsequently. Therefore, in some specific embodiments, the ratio of the mass of the lithium salt to the mass of the ionic liquid can be 1: (5~10), for example, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any value between any two of the above numerical ranges. In this way, the performance of the gel electrolyte formed subsequently can be improved, thereby further ensuring the performance of the battery.

[0089] When the ratio of the mass of the prepolymer to the mass of the ionic liquid is small, the content of the prepolymer in the electrolyte precursor is relatively low, and the content of the ionic liquid is relatively high, which is not conducive to forming a gel electrolyte with stable structure and performance through polymerization reaction. When the ratio of the mass of the prepolymer to the mass of the ionic liquid is large, the content of the prepolymer in the electrolyte precursor is relatively high, and the content of the ionic liquid is relatively low, which may cause the prepolymer to be unable to undergo sufficient polymerization reaction, thereby affecting the performance of the formed gel electrolyte. Therefore, in some specific embodiments, the ratio of the mass of the prepolymer to the mass of the ionic liquid can be (0.05~0.15):1, for example, it can be 0.05:1, 0.1:1, 0.15:1 or any value between any two of the above numerical ranges. In this way, it can better ensure that the hexafluorophosphate and / or tetrafluoroborate in the ionic liquid are thermally decomposed to produce a strong Lewis acid (PF5 and / or BF3), so that the epoxy ring-opening polymerization reaction in the prepolymer is more fully and completely carried out, thereby better improving the performance of the formed gel electrolyte.

[0090] In some embodiments, the prepolymer includes a cross-linked product of a first monomer and a second monomer, the first monomer includes at least one of the compounds having a structure as shown in formula (II), and the second monomer includes at least one of the compounds having a structure as shown in formula (III).

[0091] ;

[0092] Formula II

[0093] ;

[0094] Formula III

[0095] In the above formula II and formula III, a, b and c are all natural numbers, and R is a H atom or a methyl group.

[0096] In the embodiment of the present application, the first monomer includes a flexible segment, the second monomer includes a rigid segment, and the prepolymer obtained by cross-linking the first monomer and the second monomer has both a flexible segment and a rigid segment. Furthermore, the three-dimensional cross-linked network structure of the gel electrolyte formed by the polymerization reaction of the prepolymer has both a rigid segment and a flexible segment, so that the gel electrolyte has good structural stability and elasticity. The gel electrolyte can be used as an artificial protective layer for the negative electrode material, can better inhibit the growth of lithium dendrites during the cycle process, and can adapt to the larger volume change of the negative electrode material, thereby effectively improving the cycle performance and safety performance of the battery.

[0097] More specifically, the first monomer may include 2-methoxyethyl 2-acrylate (2-MTA) having a CAS of 3121-61-7, and the second monomer may include glycidyl methacrylate (GMA) having a CAS of 106-91-2.

[0098] The present application also provides a method for preparing an electrolyte precursor. Figure 1 The method for preparing an electrolyte precursor provided in an embodiment of the present application comprises the following steps:

[0099] S1: mixing a first monomer, a second monomer, an initiator and a solvent to perform a first cross-linking polymerization reaction to form a prepolymer;

[0100] The first monomer includes at least one of the compounds having a structure as shown in formula (II), and the second monomer includes at least one of the compounds having a structure as shown in formula (III);

[0101] ;

[0102] Formula II

[0103] ;

[0104] Formula III

[0105] Wherein, a, b and c are all natural numbers, and R is a H atom or a methyl group;

[0106] S2: Evenly mix the lithium salt, the ionic liquid and the prepolymer to obtain an electrolyte precursor, wherein the ionic liquid comprises at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinyl ionic liquid containing hexafluorophosphate and a pyrrolidinyl ionic liquid containing tetrafluoroborate.

[0107] In the embodiment of the present application, a prepolymer is first formed by a cross-linking polymerization reaction of a first monomer and a second monomer, and then an electrolyte precursor is obtained by mixing a lithium salt, an ionic liquid and a prepolymer. Since the first monomer and the second monomer include a flexible segment and a rigid segment respectively, the prepolymer has both a flexible segment and a rigid segment. The hexafluorophosphate (PF6 - ) and / or tetrafluoroborate (BF4 - ) The strong Lewis acid (PF5 and / or BF3) generated by thermal decomposition can be used as a cationic polymerization initiator to initiate the epoxy ring-opening polymerization in the prepolymer. Therefore, the subsequent heating of the electrolyte precursor can form a gel electrolyte through a polymerization reaction. No additional initiator is required, which can avoid the problem of battery performance deterioration caused by initiator residues. The three-dimensional cross-linked network structure of the formed gel electrolyte has both rigid segments and flexible segments, which can make the gel electrolyte have good structural stability and elasticity. The gel electrolyte can be used as an artificial protective layer for the negative electrode material. The piperidine or pyrrolidine cation in the ionic liquid has a relatively negative reduction potential, which can improve the electrochemical stability and interfacial chemical stability of the gel electrolyte, thereby ensuring the cycle performance of the battery. In addition, the gel electrolyte formed by the polymerization of the prepolymer contains multiple ether oxygen bonds, which can react with Li + To coordinate and complex, enhance Li + The migration of lithium ions can be improved, the ionic conductivity can be improved, and the uniform deposition and stripping of lithium ions can be promoted. Therefore, the growth of lithium dendrites can be better inhibited during the battery cycle, and the large volume change of the negative electrode material can be adapted, thereby effectively improving the cycle performance and safety performance of the battery.

[0108] In step S1, the first monomer and the second monomer are cross-linked through a carbon-carbon double bond, and the soft segment in the first monomer and the rigid segment in the second monomer are copolymerized to obtain a prepolymer. Specifically, the first monomer may include, for example, 2-methoxyethyl 2-acrylate (2-MTA); the second monomer may include, for example, glycidyl methacrylate (GMA). The cross-linking polymerization reaction formula of 2-MTA and GMA is:

[0109] ;

[0110] Wherein, a and b are both natural numbers.

[0111] There is no particular limitation on the types of initiator and solvent in step S1, and they can be selected according to actual needs.

[0112] The initiator can be any initiator known to those skilled in the art to achieve the initiation reaction. For example, the initiator can include at least one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide.

[0113] Exemplarily, the solvent may include an organic solvent, specifically, for example, at least one of N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, and toluene.

[0114] In some specific embodiments, the ratio of the total mass of the first monomer and the second monomer to the mass of the solvent may be 1:(2-5), for example, 1:2, 1:3, 1:4, 1:5 or any value between any two of the above numerical ranges. In this way, the first monomer and the second monomer can be fully dissolved in the solvent, which is convenient for free radical copolymerization by solution polymerization, that is, the first monomer and the second monomer can undergo cross-linking polymerization.

[0115] In some specific embodiments, the ratio of the mass of the first monomer to the mass of the second monomer may be 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4, 1:5 or any value between any two of the above ranges. This ensures that the first monomer and the second monomer undergo sufficient cross-linking polymerization to obtain a prepolymer of higher quality.

[0116] When the amount of the initiator added is low, it is not conducive to the full progress of the first cross-linking polymerization reaction in step S1, which will affect the amount of the obtained prepolymer. When the amount of the initiator added is high, it is easy to cause initiator residues, which will affect the quality of the obtained prepolymer. Therefore, in some specific embodiments, the ratio of the total mass of the first monomer and the second monomer to the mass of the initiator can be 1: (0.01~0.02), for example, it can be 1: 0.01, 1: 0.015, 1: 0.02 or any value between any two of the above numerical ranges.

[0117] In some specific embodiments, the temperature of the first cross-linking polymerization reaction may be 60° C. to 90° C., for example, 60° C., 70° C., 80° C., 90° C., or any value between any two of the above numerical ranges. In this way, the first monomer and the second monomer can undergo a cross-linking polymerization reaction quickly, uniformly, and fully under the action of the initiator, thereby further improving the yield and quality of the prepolymer.

[0118] In some specific embodiments, the first cross-linking polymerization reaction time may be 12 hours to 36 hours, for example, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours, 28 hours, 30 hours, 32 hours, 36 hours, or any value between any two of the above numerical ranges. This can further ensure that the first monomer and the second monomer undergo a sufficient and complete cross-linking polymerization reaction.

[0119] As a specific example, step S1 may include the following steps: first, add the first monomer, the second monomer and the initiator to a reaction bottle (for example, a Schlenk bottle) containing the above-mentioned solvent, stir evenly to make the components fully miscible, then degas through liquid nitrogen circulation (for example, three times) to remove all oxygen in the system, then place the reaction bottle in an environment of 60°C to 90°C, react for 12h to 36h, then place it in liquid nitrogen for quenching, and collect the precipitate by centrifugation to obtain a prepolymer.

[0120] In some embodiments, after step S1, the method for preparing the electrolyte precursor may further include: adding the prepolymer to a solvent for washing to remove the residual initiator, the first monomer, and the second monomer. This can prevent the initiator, the first monomer, and the second monomer from remaining in the electrolyte precursor, thereby avoiding the problem of battery performance deterioration caused by the residual initiator, the first monomer, and the second monomer.

[0121] In the actual process, for example, the precipitate obtained in the above embodiment can be added to the solvent described in the above embodiment, and the precipitate can be collected by ultrasonic cleaning and centrifugation. In the specific operation, multiple cleanings (for example, three times) can be performed to relatively completely remove the residual first monomer, second monomer and initiator to obtain the final prepolymer.

[0122] The lithium salt in step S2 may include, for example, at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate; the ionic liquid may include, for example, at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate, N-alkyl-N-methylpiperidinium tetrafluoroborate, N-alkyl-N-methylpyrrolidine hexafluorophosphate and N-alkyl-N-methylpyrrolidine tetrafluoroborate.

[0123] In some specific embodiments, the ratio of the mass of the lithium salt to the mass of the ionic liquid may be 1:(5-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any value between any two of the above ranges. This can improve the performance of the gel electrolyte formed subsequently, thereby ensuring the performance of the battery.

[0124] In some specific embodiments, the ratio of the mass of the prepolymer to the mass of the ionic liquid can be (0.05-0.15):1, for example, 0.05:1, 0.1:1, 0.15:1 or any value between any two of the above numerical ranges. This can better ensure the hexafluorophosphate (PF6 - ) and / or tetrafluoroborate (BF4 -) decomposes upon heating to produce strong Lewis acids (PF5 and / or BF3), which allow the epoxy ring-opening polymerization reaction in the prepolymer to proceed more fully and completely, thereby further improving the performance of the formed gel electrolyte.

[0125] As a specific example, step S2 may include the following steps: first, adding lithium salt to the ionic liquid and stirring evenly to obtain a mixed solution, then adding the prepolymer prepared in step S1 to the mixed solution at room temperature, and stirring evenly to obtain an electrolyte precursor.

[0126] An embodiment of the present application further provides a battery, comprising a gel electrolyte, wherein the gel electrolyte is obtained by heating the electrolyte precursor described in the above embodiment or the electrolyte precursor obtained by the preparation method described in the above embodiment.

[0127] It should be understood that since the gel electrolyte of the battery in the embodiment of the present application is obtained by heating the electrolyte precursor described in the above embodiment or the electrolyte precursor prepared by the preparation method described in the above embodiment and performing a cross-linking polymerization reaction, the beneficial effects of the electrolyte precursor in the above embodiment are all applicable to the battery.

[0128] The present application also provides a method for preparing a battery. Figure 2 The method for preparing a battery provided in the embodiment of the present application comprises the following steps:

[0129] Step S21: providing a battery cell, wherein the battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence;

[0130] Step S22: adding the electrolyte precursor described in the above embodiment or the electrolyte precursor prepared by the preparation method described in the above embodiment into the battery cell, and performing a second cross-linking polymerization reaction under heating conditions to form a gel electrolyte in the battery cell.

[0131] In the embodiment of the present application, the electrolyte precursor is added to the battery cell without the need to add an additional initiator. The electrolyte precursor can be polymerized in situ by heating to form a gel electrolyte. Compared with the situation where a thermal initiator or a photoinitiator needs to be added to the system to form a gel electrolyte, the problem of the residual initiator inducing interfacial side reactions and causing the deterioration of the battery performance can be avoided. Moreover, the in situ polymerization in the battery cell to form a gel electrolyte can effectively solve the problem of high interface resistance between the gel electrolyte and the electrode, thereby further improving the cycle performance of the battery.

[0132] In step S22, the reaction formula of the second cross-linking polymerization reaction is:

[0133] ;

[0134] Wherein, a and b are both natural numbers.

[0135] In some embodiments, the temperature of the second cross-linking polymerization reaction in step S22 can be 70°C to 90°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C or any value between any two of the above numerical ranges. In this way, on the one hand, the hexafluorophosphate and / or tetrafluoroborate in the ionic liquid of the electrolyte precursor can be fully decomposed by heat to produce a strong Lewis acid to initiate the epoxy ring-opening polymerization in the prepolymer, so that the second cross-linking polymerization reaction is relatively sufficient and complete, thereby ensuring the performance of the formed gel electrolyte, and on the other hand, it can avoid excessive temperature and affect other structures in the battery cell.

[0136] In some embodiments, the second cross-linking polymerization reaction in step S22 may be carried out for 0.5 h to 5 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h or any value between any two of the above ranges. This can better ensure that the electrolyte precursor reacts fully to form a high-quality gel electrolyte, thereby further improving the performance of the battery.

[0137] In some embodiments, the negative electrode sheet in the above battery cell may include metallic lithium.

[0138] Due to the high reactivity of metallic lithium, the side reactions between the lithium metal negative electrode and the electrolyte are serious, and the solid electrolyte interface film formed at the interface between the negative electrode and the electrolyte is unstable, which can easily cause excessive growth of lithium dendrites and drastic volume changes in the negative electrode material, thereby seriously affecting the cycle performance and safety performance of the battery. The three-dimensional cross-linked network structure of the gel electrolyte formed by the electrolyte precursor in the embodiment of the present application has both rigid segments and flexible segments, so that the gel electrolyte has good structural stability and elasticity. The gel electrolyte can be used as an artificial protective layer for the negative electrode material. The piperidine or pyrrolidino cation in the ionic liquid has a relatively negative reduction potential, which can improve the electrochemical stability and interfacial chemical stability of the gel electrolyte, thereby ensuring the cycle performance of the battery. Moreover, the gel electrolyte formed by the polymerization of the prepolymer contains multiple ether oxygen bonds, which can react with Li + To coordinate and complex, enhance Li + The migration of lithium ions can be improved, the ion conductivity can be improved, and then the uniform deposition and stripping of lithium ions can be promoted. Therefore, the growth of lithium dendrites can be better inhibited during the battery cycle, and the large volume change of the negative electrode material can be adapted to effectively improve the cycle performance and safety performance of the battery. It is more suitable for batteries that include metallic lithium in the negative electrode sheet.

[0139] As a specific example, the electrolyte precursor can be added to the dry cell of the lithium metal battery, and after being fully wetted after packaging, the cell is placed in an oven and reacted at a temperature of 70°C to 90°C for 0.5h to 5h to ensure that the electrolyte precursor is completely reacted to obtain a gel electrolyte. Among them, the negative electrode of the lithium metal battery can be a lithium copper composite strip with lithium on both sides, and the positive electrode material can be, for example, lithium iron phosphate (LiFePO4) or a ternary positive electrode material, and the ternary positive electrode material can be, for example, lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA).

[0140] It should be noted that the in-situ formation of gel electrolyte in the battery cell in the above embodiment is only an example. In some other embodiments of the present application, a gel electrolyte can be formed on the surface of any one or more of the positive electrode sheet, the separator, and the negative electrode sheet, and then the positive electrode sheet, the separator, and the negative electrode sheet are assembled to obtain a battery. Specifically, for example, the positive electrode sheet, the separator, and the negative electrode sheet can be immersed in the electrolyte precursor to fully soak (for example, standing for 10 minutes), then taken out, and then placed in a vacuum drying oven for heating to form a gel electrolyte on the surface of the positive electrode sheet, the separator, and the negative electrode sheet.

[0141] In some embodiments, after forming a gel electrolyte on the surface of one or both of the positive electrode sheet and the negative electrode sheet, the positive electrode sheet and the negative electrode sheet can be directly assembled to obtain a battery. That is, the formed battery may not include a separator because the gel electrolyte itself can play the role of a separator.

[0142] The present application also provides a battery, which is manufactured using the battery manufacturing method described in the above embodiment.

[0143] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples. Example 1

[0144] The preparation of the electrolyte precursor in this embodiment includes the following steps:

[0145] S101: First, add the first monomer (2-MTA), the second monomer (GMA) and azobisisobutyronitrile (AIBN) to a Schlenk flask containing N,N-dimethylformamide (DMF), stir evenly to make the components fully miscible, wherein the mass ratio of DMF to the total mass of the two monomers is 5:1, the mass ratio of 2-MTA to GMA is 1:5, and the ratio of the initiator to the total mass of the two monomers is 0.015:1. Then, degas the system by three liquid nitrogen cycles to remove oxygen. Next, place the Schlenk flask at 70°C, react for 24 hours, place it in liquid nitrogen for quenching, collect the precipitate by centrifugation, then add the obtained precipitate to DMF, clean it by ultrasonic, collect the precipitate by centrifugation, and wash it repeatedly for 3 times to remove the remaining first monomer, second monomer and initiator to obtain the final prepolymer;

[0146] S102: First, lithium bis(fluorosulfonyl)imide (LiFSI) is added to N-propyl-N-methylpiperidinium hexafluorophosphate (ionic liquid) and stirred evenly to obtain a mixed solution, wherein the mass ratio of lithium bis(fluorosulfonyl)imide to N-propyl-N-methylpiperidinium hexafluorophosphate is 1:7. Next, the prepolymer obtained in step S101 is added to the mixed solution at room temperature and stirred evenly to obtain an electrolyte precursor, wherein the mass ratio of the prepolymer to N-propyl-N-methylpiperidinium hexafluorophosphate is 0.1:1.

[0147] The preparation of the battery in this embodiment includes the following steps:

[0148] S201: Preparation of lithium metal battery dry cells: Ternary positive electrode materials (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black (Super-P), multi-walled carbon nanotubes (MWCNT) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.5:1:0.25:1.25, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry, and the positive electrode slurry is coated on a 12μm aluminum foil, and after drying, it is rolled, slit and cut into pieces to obtain a lithium metal battery positive electrode sheet; a lithium copper composite belt with 25μm metallic lithium on both sides is cut into pieces to obtain a lithium metal battery negative electrode sheet; the positive electrode sheet, polypropylene separator and negative electrode sheet are assembled in a stacked manner to obtain a battery electrode group, and the battery electrode group is assembled in an aluminum-plastic film, and dried in a vacuum drying oven to obtain a lithium metal battery dry cell to be injected with liquid;

[0149] S202: Add the electrolyte precursor prepared in the above step S102 to the lithium metal battery dry cell obtained in step S201, and after packaging and sufficient infiltration, place the cell in an oven and react at 70°C for 5 hours to ensure that the electrolyte precursor is completely reacted to form a gel electrolyte to obtain a lithium metal battery. Example 2

[0150] The preparation of the electrolyte precursor in this embodiment is basically the same as that in Embodiment 1, except that in step S101, the mass ratio of 2-MTA to GMA is 1:2.

[0151] The preparation of the battery in this embodiment is basically the same as that in Embodiment 1, except that in step S202, the electrolyte precursor prepared in Embodiment 2 is added to the lithium metal battery dry cell obtained in step S201. Example 3

[0152] The preparation of the electrolyte precursor in this embodiment is basically the same as that in Example 1, except that in step S102, the mass ratio of lithium bis(fluorosulfonyl)imide to N-propyl-N-methylpiperidinium hexafluorophosphate is 1:10, and the mass ratio of the prepolymer to N-propyl-N-methylpiperidinium hexafluorophosphate is 0.15:1.

[0153] The preparation of the battery in this embodiment is basically the same as that in Embodiment 1, except that in step S202, the electrolyte precursor prepared in Embodiment 3 is added to the lithium metal battery dry cell obtained in step S201. Example 4

[0154] The preparation of the electrolyte precursor in this embodiment is basically the same as that in Embodiment 1, except that the ionic liquid in step S102 is N-ethyl-N-methylpiperidinium tetrafluoroborate.

[0155] The preparation of the battery in this embodiment is basically the same as that in Embodiment 1, except that in step S202, the electrolyte precursor prepared in Embodiment 4 is added to the lithium metal battery dry cell obtained in step S201. Example 5

[0156] The preparation of the electrolyte precursor in this embodiment is the same as that in Embodiment 1.

[0157] The preparation of the battery in this embodiment includes the following steps:

[0158] Step S201: Prepare a lithium metal battery dry cell: Prepare a ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black (Super-P), multi-walled carbon nanotubes (MWCNT) and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.5:1:0.25:1.25, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry. The positive electrode slurry is coated on a 12μm aluminum foil, and after drying, it is rolled, slit and cut into pieces to obtain a lithium metal battery positive electrode sheet. The lithium copper composite tape with 25μm metal lithium on both sides is cut into pieces to obtain a lithium metal battery negative electrode sheet;

[0159] Step S202: completely immerse the glass fiber separator in the electrolyte precursor prepared in the above Example 1 to fully wet it, let it stand for 10 minutes, then take it out, and then place it in a vacuum drying oven to react at 70° C. for 5 hours to obtain a gel electrolyte;

[0160] Step S203: Assemble the positive electrode sheet obtained in step S201, the separator obtained in step S202, and the negative electrode sheet obtained in step S201 in a stacking manner to obtain a battery electrode group, place the battery electrode group in an aluminum-plastic film and package it to obtain a lithium metal battery.

[0161] Comparative Example 1

[0162] The preparation of the electrolyte precursor in this comparative example is basically the same as that in Example 1, except that the ionic liquid in step S102 is 1,3-dimethylimidazolium tetrafluoroborate (CAS No.: 121091-31-4).

[0163] The preparation of the battery in this comparative example is basically the same as that in Example 1, except that in step S202, the electrolyte precursor prepared in comparative example 1 is added to the lithium metal battery dry cell obtained in step S201.

[0164] Comparative Example 2

[0165] The preparation of the electrolyte precursor in this comparative example is basically the same as that in Example 1, except that the ionic liquid in step S102 is N-ethyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide salt (CAS No.: 927820-65-3).

[0166] The preparation of the battery in this comparative example is basically the same as that in Example 1, except that in step S202, the electrolyte precursor prepared in comparative example 2 is added to the lithium metal battery dry cell obtained in step S201.

[0167] The electrolyte precursors obtained in the above-mentioned embodiments and comparative examples were prepared into gel electrolytes, and electrochemical window tests were performed.

[0168] The specific test method is as follows: first, a "stainless steel sheet / diaphragm / lithium sheet" R2032 button blocking battery is assembled by stacking stainless steel sheets, diaphragms and lithium sheets in sequence, and 100 μL of the electrolyte precursor obtained in the above embodiments and comparative examples is added to the battery, and then the battery is placed in an oven and reacted at 70°C for 5 hours to ensure that the electrolyte precursor is completely reacted to form a gel electrolyte. Then, the electrochemical window of the gel solid electrolyte is tested by linear sweep voltammetry, with a scan rate of 0.1 mV / s, from the open circuit voltage forward to 6V. The test results are shown in Table 1.

[0169] The cycle performance of the lithium metal batteries obtained in the above embodiments and comparative examples was tested.

[0170] The specific test method is: use the Blue Electric charge and discharge tester to test the cycle performance of the battery at 25°C. First, charge the battery to 4.2V at a constant current of 0.2C, then charge to 0.05C at a constant voltage at 4.2V, and finally discharge to 2.5V at a constant current of 1C. The capacity is recorded as C0. After 500 cycles of this procedure, the capacity at this time is recorded as C1, and the capacity retention rate = (C1 / C0) × 100%. The test results are shown in Table 1.

[0171] Table 1

[0172]

[0173] From the data in Table 1, it can be seen that the electrolytes obtained after heating the electrolyte precursors prepared in Examples 1 to 5 and Comparative Example 1 are all in a gel state, but the electrochemical window of the gel electrolyte obtained after heating the electrolyte precursors prepared in Examples 1 to 5 is significantly higher than the electrochemical window of the gel electrolyte obtained after heating the electrolyte precursor prepared in Comparative Example 1. This shows that the piperidine or pyrrolidinyl cation in the ionic liquid in the present application has a relatively negative reduction potential, which can improve the electrochemical stability and interfacial chemical stability of the gel electrolyte, so that the electrochemical window of the gel electrolyte is higher, while the imidazolium cation in the ionic liquid in Comparative Example 1 has poor chemical stability and is easily reduced at the negative electrode, resulting in a low electrochemical window of the gel electrolyte. In Comparative Example 2, since the ionic liquid does not include hexafluorophosphate and / or tetrafluoroborate, a strong Lewis acid (PF5 and / or BF3) cannot be generated under heating conditions to initiate epoxy ring-opening polymerization in the prepolymer, so an electrolyte in a gel state cannot be obtained. Since the ionic liquid in Comparative Example 2 also includes piperidinium cations having a relatively negative reduction potential, the electrochemical window of the electrolyte is relatively high.

[0174] It can be seen from the data in Table 1 that the capacity retention rate of the battery in Examples 1 to 5 after 500 cycles is higher than that of the battery in Comparative Example 1 after 500 cycles, which shows that the gel electrolyte formed by the electrolyte precursor prepared in the present application has high electrochemical stability and interfacial chemical stability, which can guarantee the cycle performance of the battery. The three-dimensional cross-linked network structure of the gel electrolyte has both rigid segments and flexible segments, so that the gel electrolyte can be used as an artificial protective layer of the negative electrode material, which can better inhibit the growth of lithium dendrites during the cycle and adapt to the large volume change of the negative electrode material, thereby effectively improving the cycle performance and safety performance of the battery. In addition, the capacity retention rate of the battery in Example 5 is lower than that of the battery in Examples 1 to 4, which shows that by forming a gel electrolyte by in-situ polymerization in the battery cell, the problem of high interface resistance between the gel electrolyte and the electrode can be effectively solved, so the cycle performance of the battery can be further improved. That is, in the present application, forming a gel electrolyte by in-situ polymerization in the battery cell is a more preferred solution.

[0175] For Comparative Example 2, although the ionic conductivity of the liquid electrolyte is relatively high, which can improve the capacity retention rate of the battery to a certain extent, since no gel electrolyte is formed, the capacity retention rate of the battery in Comparative Example 2 is still lower than the capacity retention rate of the battery in Example 1. This shows that the gel electrolyte can be used as an artificial protective layer for the negative electrode material, can better inhibit the growth of lithium dendrites during the cycle process, and can adapt to the larger volume change of the negative electrode material, thereby better improving the cycle performance and safety performance of the battery.

[0176] It should be noted that the electrolyte precursor embodiments, electrolyte precursor preparation method embodiments, battery preparation method embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.

[0177] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. An electrolyte precursor, characterized in that: It comprises a lithium salt, an ionic liquid and a prepolymer; the ratio of the mass of the lithium salt to the mass of the ionic liquid is 1:(5-10); the ratio of the mass of the prepolymer to the mass of the ionic liquid is (0.05-0.15):1; The ionic liquid includes at least one of a piperidinium ionic liquid containing hexafluorophosphate, a piperidinium ionic liquid containing tetrafluoroborate, a pyrrolidinium ionic liquid containing hexafluorophosphate, and a pyrrolidinium ionic liquid containing tetrafluoroborate; The structural formula of the prepolymer is shown in formula (I): ; Formula I Wherein, a, b, c, m and n are all natural numbers, and R is a H atom or a methyl group.

2. The electrolyte precursor according to claim 1, characterized in that The electrolyte precursor satisfies at least one of the following characteristics: (1) The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate; (2) The ionic liquid includes at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate, N-alkyl-N-methylpiperidinium tetrafluoroborate, N-alkyl-N-methylpyrrolidine hexafluorophosphate, and N-alkyl-N-methylpyrrolidine tetrafluoroborate; (3) The prepolymer comprises a cross-linked product of a first monomer and a second monomer, wherein the first monomer comprises at least one of the compounds having a structure represented by formula (II), and the second monomer comprises at least one of the compounds having a structure represented by formula (III); ; Formula II ; Formula III Wherein, a, b and c are all natural numbers, and R is a H atom or a methyl group.

3. A method for preparing an electrolyte precursor, characterized in that: The following steps are involved: S1: mixing a first monomer, a second monomer, an initiator and a solvent to perform a first cross-linking polymerization reaction to form a prepolymer; the ratio of the mass of the first monomer to the mass of the second monomer is 1:(1-5); The first monomer includes at least one of the compounds having a structure as shown in formula (II), and the second monomer includes at least one of the compounds having a structure as shown in formula (III); ; Formula II ; Formula III Wherein, a, b and c are all natural numbers, and R is a H atom or a methyl group; S2: Evenly mix the lithium salt, the ionic liquid and the prepolymer to obtain the electrolyte precursor, wherein the ionic liquid includes at least one of a piperidine ionic liquid containing hexafluorophosphate, a piperidine ionic liquid containing tetrafluoroborate, a pyrrolidone ionic liquid containing hexafluorophosphate, and a pyrrolidone ionic liquid containing tetrafluoroborate; the ratio of the mass of the lithium salt to the mass of the ionic liquid is 1:(5~10); the ratio of the mass of the prepolymer to the mass of the ionic liquid is (0.05~0.15):

1.

4. The method for preparing an electrolyte precursor according to claim 3, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The first monomer includes 2-methoxyethyl 2-acrylate; (2) the second monomer comprises glycidyl methacrylate; (3) The initiator includes at least one of azobisisobutyronitrile, sodium persulfate, and tert-butyl peroxide; (4) The solvent includes at least one of N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide, and toluene; (5) The ratio of the total mass of the first monomer and the second monomer to the mass of the solvent is 1:(2-5); (6) The ratio of the total mass of the first monomer and the second monomer to the mass of the initiator is 1:(0.01-0.02); (7) The temperature of the first cross-linking polymerization reaction is 60°C to 90°C; (8) The time of the first cross-linking polymerization reaction is 12h~36h.

5. The method for preparing an electrolyte precursor according to claim 3, characterized in that: Step S2 satisfies at least one of the following characteristics: (1) The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate) and lithium difluorophosphate; (2) The ionic liquid includes at least one of N-alkyl-N-methylpiperidinium hexafluorophosphate, N-alkyl-N-methylpiperidinium tetrafluoroborate, N-alkyl-N-methylpyrrolidine hexafluorophosphate, and N-alkyl-N-methylpyrrolidine tetrafluoroborate.

6. The method for preparing an electrolyte precursor according to any one of claims 3 to 5, characterized in that: After step S1, the method for preparing the electrolyte precursor further comprises: The prepolymer is added into the solvent for washing to remove the residual initiator, the first monomer and the second monomer.

7. A battery, characterized in that: The invention comprises a gel electrolyte, wherein the gel electrolyte is obtained by heating the electrolyte precursor according to claim 1 or 2 or the electrolyte precursor obtained by the preparation method according to any one of claims 3 to 6.

8. A method for preparing a battery, characterized in that: The following steps are involved: Providing a battery cell, the battery cell comprising a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence; The electrolyte precursor according to claim 1 or 2 or the electrolyte precursor prepared by the preparation method according to any one of claims 3 to 6 is added to the battery cell, and a second cross-linking polymerization reaction is carried out under heating conditions to form a gel electrolyte in the battery cell.

9. The method for preparing a battery according to claim 8, characterized in that: The method satisfies at least one of the following features: (1) The temperature of the second cross-linking polymerization reaction is 70°C to 90°C; (2) The time of the second cross-linking polymerization reaction is 0.5h~5h; (3) The negative electrode sheet includes metallic lithium.

10. A battery, characterized in that: The battery is prepared by the method for preparing the battery according to claim 8 or 9.

Citation Information

Patent Citations

  • Autocatalytic gel polymer electrolyte, and preparation method and application thereof

    CN116544497A

  • Lithium metal battery and preparation method thereof

    CN118248957A